The response of the stem sap flow dynamics of Tamarix ramosissima to rainfall variability in the desert-oasis transition zone of Northwest China - Liu, Feiyao; Zhang, Lijuan; You, Quangang; Xue, Xian; Liu, Guohua; Feng, Chang (Frontiers in Plant Science, 2025)
Plant transpiration is a fundamental process for maintaining the water cycle, regulating temperature and facilitating nutrient uptake, while also playing a critical role in climate regulation and ecosystem services. However, a significant knowledge gap remains in the understanding of how plant transpiration responds to changes in precipitation patterns within dryland ecosystems. In the present study, the stem sap flow of the phreatophyte xerophytic shrub Tamarix ramosissima, meteorological factors, soil moisture content, and bare soil evaporation were examined to assess the effects of two different rainfall categories (category I: lower mean rainfall amount and duration; category II: higher mean rainfall amount and duration) on stem sap flow dynamics. Our results reveal that the rainfall reduced the stem sap flow by 46.5% and 29.5% compared to the previous days across rainfall category I and II, respectively. The daily and diurnal variation of stem sap flow during the three days following rainfall showed non-significant variation compared to pre-rainfall, regardless of rainfall category. The soil moisture content at depth of 0–40 cm (SMC0-40cm) exhibits a pronounced increase to rainfall events, irrespective of rainfall category, although these events did not significantly increase the soil available moisture content within this depth. Concurrently, the weighing micro-lysimeters utilized in this study revealed that approximately 91.5% of the total precipitation during the experimental period evaporated into the atmosphere. In addition, the daily stem sap flow on the rainfall day and the following three days post rainfall was strongly positively correlated with photosynthetically active radiation, air temperature, and vapor pressure deficit within the two rainfall categories rather than with SMC0-40cm. Together, our findings indicate that the effects of rainfall variability on stem sap flow of T. ramosissima are primarily driven by meteorological factors, independent of the rainfall category. The results of this study provide a valuable insight for assessing species-specific water-use strategies and implementing effective reforestation practices in the future.